COMPETENCIES OF WEST SULAWESI MATHEMATICS TEACHERS FROM STUDENTS' PERSPECTIVES - Fadhil Zil Ikram; Nursyam Anaguna; Rosidah; Muhammad Takwin Machmud (UNMUHBABEL Press, 2024)
This qualitative study aims to describe the competencies of mathematics teachers from the perspective of secondary school students in West Sulawesi, especially related to which aspects need to be developed. Data collection in this study used a survey with open-ended questions that asked students to submit responses, criticisms, or suggestions regarding their teachers' performance in learning mathematics. The survey lasted for 4 weeks, in July 2024. The population of this study was all secondary school students in West Sulawesi and the sample of this study was 1012 students consisting of 559 high school students and 453 junior high school students in West Sulawesi. Data analysis techniques in this study employed three stages consisting of data condensation, data display, and conclusion drawing. The findings showed that there are still numerous secondary school students (junior and senior high school) in West Sulawesi who are not satisfied with the mathematics learning they experience, particularly regarding the competence of their mathematics teachers. From the students' viewpoint, there are still numerous aspects of the four competencies of secondary school mathematics teachers (personality, pedagogic, professional, and social) in West Sulawesi that need to be further developed.